Cost-effectiveness of HPV vaccination for adults through age 45 years in the United States: Estimates from a simplified transmission model. Issue 50 (25th November 2020) - Chesson, Harrell W.; Meites, Elissa; Ekwueme, Donatus U.; Saraiya, Mona; Markowitz, Lauri E.
Abstract: Introduction: The objective of this study was to assess incremental costs and benefits of a human papillomavirus (HPV) vaccination program expanded to include "mid-adults" (adults aged 27 through 45 years) in the United States. Methods: We adapted a previously published, dynamic mathematical model of HPV transmission and HPV-associated disease to estimate the incremental costs and benefits of a 9-valent HPV vaccine (9vHPV) program for people aged 12 through 45 years compared to a 9vHPV program for females aged 12 through 26 years and males aged 12 through 21 years. Results: A 9vHPV program for females aged 12 through 26 years and males aged 12 through 21 years was estimated to cost < $10, 000 quality-adjusted life year (QALY) gained, compared to no vaccination. Expanding the 9vHPV program to include mid-adults was estimated to cost $587, 600 per additional QALY gained when including adults through age 30 years, and $653, 300 per additional QALY gained when including adults through age 45 years. Results were most sensitive to assumptions about HPV incidence among mid-adults, current and historical vaccination coverage, vaccine price, and the impact of HPV diseases on quality of life. Conclusions: Mid-adult vaccination is much less cost-effective than the comparison strategy of routine vaccination for all adolescents at ages 11 to 12 years and catch-up vaccination for women through age 26 years and men through age 21 years.